The Legal Status of Customary Villages within the Framework of Special Autonomy in Papua A Perspective on Legal Politics - Frans Reumi; Tom Alfa Samuel Reumy (Ipso Jure, 2024)
The purpose of this article is to explore the normative perspective of legal politics in applying the principle of decentralization, which grants authority to regions to regulate and manage their governance. This principle is manifested in regional autonomy and special autonomy for certain regions, such as Aceh, Papua, and West Papua, with constitutional foundations in Articles 1, 18, 18A, 18B (1) and (2), and 28I (3) of the 1945 Constitution of the Republic of Indonesia. These articles provide the legal basis for recognizing special regions and areas governed by laws, as stipulated in Article 399 of Law Number 23 of 2014, and Articles 94 to 111 of Law Number 6 of 2014. Regarding special autonomy in Papua, both philosophical and juridical aspects are addressed by Law Number 2 of 2021, which amends Law Number 21 of 2001 on Special Autonomy for Papua Province. This is supported by Government Regulations Number 106 and 107 of 2021, and further enforced by regional regulations, such as Papua Province Regional Regulation Number 3 of 2022 and Jayapura Regency Regional Regulation Number 1 of 2022 concerning Customary Villages. These regulations provide the legal framework for the nine customary law communities in the Tabi/Mamta area of Jayapura Regency. From a sociological perspective, these customary villages function within a traditional leadership system, led by senior figures known as Ondofolo (Ondoafi), reflecting the embedded customary institutional framework..